A institucionalização escolar da prática do skate no currículo de Educação Física da Rede Pública Estadual de São Paulo (2010 a 2018) - Santoni, João Henrique (2020)
The practice and the cultural universe of skateboarding are marked by historical and social transformations that can be identified through four moments: leisure, the sporting process, cultural transgression and the relationship between skateboarding and education. The relationship between skateboarding and education is marked by two types of analysis: one linked to Physical Education that argues about the educational possibilities of skateboarding, and another line that identifies conflicts in the relationships between skateboarders and the school institution. The research intends to verify these questions by analyzing the curriculum of Physical Education in High School, third year, through the Notebook of the Teacher and the Student of the Secretary of Education of the State of São Paulo. It aims to identify how the practice of skateboarding and the pedagogical project that underlies it are conceived in the curriculum, as well as the potential and limits of skateboarding in the school space. The time frame will run from 2010 (year in which the Curriculum Proposal becomes the Official Curriculum of the State of São Paulo) until 2018, (year of the beginning of this research). The authors that support the research are: Goodson (1995), Sacristán (1988), and Apple (1989) for the discussion on curriculum; Dominique Julia (2001) and Viñao Frago (2006) for the concept of school culture; Honorato (2004), Brandão (2006) to debate the history and practice of skateboarding; Boim, (2010), Almeida Neto and Ciampi (2015) and Ribeiro (2015) to discuss the São Paulo Faz Escola Program. The research confirmed the working hypotheses: although present in the curricular content, the practice of skateboarding does not materialize because it disregards the objective working conditions, the school culture and the teaching knowledge